H3K27me3 loss indicates an increased risk of recurrence in the Tübingen meningioma cohort. Issue 8 (23rd December 2020) - Behling, Felix; Fodi, Christina; Gepfner-Tuma, Irina; Kaltenbach, Kristina; Renovanz, Mirjam; Paulsen, Frank; Skardelly, Marco; Honegger, Jürgen; Tatagiba, Marcos; ,; Schittenhelm, Jens; Tabatabai, Ghazaleh
Abstract: Background: A loss of the trimethylation of lysine 27 of histone H3 (H3K27me3) in meningioma has been recently suggested as an adjunct to identify subsets of higher risk of recurrence. The aim of the present study was to assess the prognostic value of H3K27 histone trimethylation and its potential clinical utility in the "Tübingen meningioma cohort." Methods: Patients who underwent meningioma resection between October 2003 and December 2015 at the University Hospital Tübingen were included. Immunohistochemical stainings for H3K27me3 and the proliferation marker MIB1 were assessed and correlated with clinical parameters using univariate and multivariate Cox regressions as well as Pearson's chi-squared and log-rank test. Results: Overall, 1268 meningiomas were analyzed with a female to male ratio of 2.6 and a mean age of 58.7 years (range 8.3–91.0). With 163 cases lost to follow up, 1103 cases were available for further analysis with a mean follow-up of 40.3 months (range 1.1–186.3). Male gender, younger age, intracranial tumor localization, progressive tumor, subtotal resection, higher WHO grade, increased MIB1 rate, and loss of H3K27me3 were significant negative prognostic factors in the univariate analysis. H3K27me3 status and all other prognostic factors, except age and tumor location, remained significant in the multivariate model. Furthermore, adjuvant radiotherapy was an independent positive prognostic factor. Conclusions: Loss of H3K27me3 combined with MIB1 labeling index are independent prognostic factors in meningioma. These data from the Tübingen meningioma cohort support the clinical utility of H3K27me3 immunohistochemical staining in meningioma and its integration into the routine histopathological workup.